Optimal allocation of operators in a cellular manufacturing system by an integrated computer simulation–genetic algorithm approach. (1st January 2011) - Azadeh, Ali; Nokhandan, Behnaz Pourvalikhan; Asadzadeh, Sayed Mohammad; Fathi, Ehsan
By noting the importance of flexible manufacturing system (FMS), variable market and reduction in product life cycle, this study presents a decision-making model for optimisation of operator allocation in a Cellular Manufacturing System (CMS) using computer simulation (CS) and genetic algorithm (GA). This study determines the number of cross-trained operators and optimum operators' layout with respect to cellular condition in a CMS by an integrated approach. The main contribution of this paper is utilisation of an integrated CS–GA approach for optimum allocation of operators in a CMS whereas previous studies only use CS or other meta-heuristics. A typical U-shaped CMS is used as the case study to show superiority and advantage of the proposed approach.